Dose response for Auricularia auricula-judae against acute gamma irradiation - Hing Jan Nie,; Azhar Mohamad,; Zaiton Abdul Kadir,; Wan Safina Wan Abdul Razak,; Ibrahim Mahmood,; Hisham Hamza Hussain, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Auricularia auricula-judae is a jelly and ear-like mushroom well known as part of traditional Chinese medicine and cuisine. Issues in mushroom cultivation are related to sustaining sufficient amount of strains with genetic variations for selection and obtaining quality strains for mother cultures. Strain selections by growers are hampered by the narrow genetic variations of existing mushrooms. Induced mutations through gamma radiation was found to significantly generate genetic variations in mushroom. This study aims to determine dose response of A. auricula-judae when irradiated with gamma radiation. Samples grown on semi solid PDA (Potato Dextrose Agar) media were exposed to gamma radiation from Cs-137 source in Biobeam GM8000. Doses for acute gamma irradiation ranged from 0 Gy, 0.1 kGy, 0.2 kGy, 0.3 kGy, 0.4 kGy, 0.5 kGy, 0.6 kGy, 0.7 kGy, 0.8 kGy, 0.9 kGy, 1.0 kGy, 1.5 kGy, 2.0 kGy and 4.0 kGy at dose rate 0.013 kGy/min. Visual observations and diameter growth measurements of mycelia were observed 2 days’ interval for 8 days. Results revealed mycelia density and growth performance decreases with increasing radiation doses. Other morphological characters of irradiated mycelia remained the same with control. LD50 for A. auricula-judae was determined at 1.5 kGy. Findings in this study are important for induced mutation studies of A. auricula-judae and benefiting to the mushroom industry.